Application of Melting Temperature in Melting Curve of qPCR to Determine Listeria monocytogenes Presence in Golden Needle Mushroom - Yeongeun Seo; Yewon Lee; Jimyeong Ha; Yohan Yoon (Journal of Food Quality)
This study developed a method to determine Listeria monocytogenes presence in golden needle mushrooms by melting temperature (Tm) in a melting curve of qPCR. For identical samples (n = 35), the results for L. monocytogenes presence determined by Tm values were compared with the results from a conventional detection method (culture-based procedures). The samples that showed the negative result in the conventional method were subsequently examined with the Tm value of qPCR. Tm values for Escherichia coli (87.5 ± 0.4°C), Salmonella (87.6 ± 0.1°C), Staphylococcus aureus (79.2 ± 0.0°C), Listeria innocua (80.5 ± 0.0°C), Listeria ivanovii (79.0 ± 0.4°C), Listeria welshimeri (78.8 ± 0.4°C), and Listeria monocytogenes (83.7 ± 0.2°C) were different, and thus, no similar Tm values of L. monocytogenes were observed with other bacteria. From 35 golden needle mushrooms, 26 samples (74.3%) were L. monocytogenes positive with Tm value of qPCR, but only 13 samples (37.1%) of 35 samples were L. monocytogenes positive using the conventional detection method. Of the samples that were positive with the Tm value of qPCR, but negative with the conventional detection method, 4 samples were selected randomly, and typical L. monocytogenes colonies were detected in CHROMagar. These results indicate that the Tm value in the melting curve of qPCR can be used to detect L. monocytogenes in golden needle mushrooms.